2006
DOI: 10.1038/modpathol.3800542
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and significance of nerve growth factor receptor (NGFR/p75NTR) in normal, benign and malignant breast tissue

Abstract: Nerve growth factor receptor (NGFR) is a transmembrane glycoprotein without intrinsic tyrosine kinase activity, whose expression is not restricted to neural cells. NGFR is reported to act as a tumour suppressor, negatively regulating cell growth and proliferation. NGFR expression was immunohistochemically analysed in normal breast tissue and in 140 benign, biphasic and preinvasive breast lesions, in 22 tumours with myoepithelial differentiation and in two cohorts of breast cancer patients: a series of 245 inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 47 publications
5
70
1
Order By: Relevance
“…Nevertheless, neither Ki67 nor PPH3 is particularly specific for the basal-like subtype, hardly surprising given that luminal B and HER2-enriched breast cancers are also characterized by strong proliferation signatures. 1,3,7 CK14, IMP3 and NGFR had the highest specificity (100%) for basal-like breast cancer but this came at the significant expense of sensitivity, which, in line with published observations, 84,109 ranged from 22% to 27%.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, neither Ki67 nor PPH3 is particularly specific for the basal-like subtype, hardly surprising given that luminal B and HER2-enriched breast cancers are also characterized by strong proliferation signatures. 1,3,7 CK14, IMP3 and NGFR had the highest specificity (100%) for basal-like breast cancer but this came at the significant expense of sensitivity, which, in line with published observations, 84,109 ranged from 22% to 27%.…”
Section: Discussionsupporting
confidence: 86%
“…Caveolin-1, a major component of caveolar membranes consistently expressed in myoepithelial cells (Hurlstone et al, 1999;Jones et al, 2004b), which is reported to have both tumour suppressive and oncogenic properties depending on the context (Hurlstone et al, 1999;Hnasko and Lisanti, 2003;Williams and Lisanti, 2005), has been shown to be expressed in a subset of basal-like and BRCA1 tumours (Charafe-Jauffret et al, 2006;Pinilla et al, 2006). Other interesting proteins preferentially expressed in myoepithelial cells and basal-like tumours are fascin (Rodriguez-Pinilla et al, 2006), osteonectin (Jones et al, 2004b;Lakhani et al, 2005), p-cadherin (Arnes et al, 2005;Jacquemier et al, 2005;CharafeJauffret et al, 2006), 14-3-3 sigma (Simpson et al, 2004), maspin (Jones et al, 2004b), alpha-beta-crystallin (Jones et al, 2004b;Moyano et al, 2006) and p75 nerve growth factor receptor (NGFR) (Reis-Filho et al, 2006d); the latter two markers appear to identify prognostically significant subgroups of basal-like breast cancers. Alpha-b-crystallin is expressed in basal-like breast cancers with pathological features suggestive of a more aggressive clinical behaviour (Moyano et al, 2006), whereas NGFR has recently been shown to be expressed in a subset of basal-like breast carcinomas with less frequent lymph node metastasis and a longer overall survival (Reis-Filho et al, 2006d).…”
Section: Morphological and Immunohistochemical Features Of Basal-likementioning
confidence: 99%
“…Other interesting proteins preferentially expressed in myoepithelial cells and basal-like tumours are fascin (Rodriguez-Pinilla et al, 2006), osteonectin (Jones et al, 2004b;Lakhani et al, 2005), p-cadherin (Arnes et al, 2005;Jacquemier et al, 2005;CharafeJauffret et al, 2006), 14-3-3 sigma (Simpson et al, 2004), maspin (Jones et al, 2004b), alpha-beta-crystallin (Jones et al, 2004b;Moyano et al, 2006) and p75 nerve growth factor receptor (NGFR) (Reis-Filho et al, 2006d); the latter two markers appear to identify prognostically significant subgroups of basal-like breast cancers. Alpha-b-crystallin is expressed in basal-like breast cancers with pathological features suggestive of a more aggressive clinical behaviour (Moyano et al, 2006), whereas NGFR has recently been shown to be expressed in a subset of basal-like breast carcinomas with less frequent lymph node metastasis and a longer overall survival (Reis-Filho et al, 2006d). These studies were carried out retrospectively in small cohorts of patients (Moyano et al, 2006;Reis-Filho et al, 2006d), and therefore the actual prognostic significance of these proteins for patients with basal-like and BRCA1 tumours remains to be determined.…”
Section: Morphological and Immunohistochemical Features Of Basal-likementioning
confidence: 99%
See 1 more Smart Citation
“…This basal-like phenotype is characterized by the expression of markers typical of the normal basal/myoepithelium such as cytokeratins 5/6, 14, 17, EGFR, p-cadherin, osteonectin, fascin, caveolin-1 which are more frequently positive in BRCA1 tumors (Palacios et al, 2003;van der Groep et al, 2004;Arnes et al, 2005;Lakhani et al, 2005;Pinilla et al, 2006;Rodriguez-Pinilla et al, 2006). Recently it has been reported that two proteins, nerve growth factor receptor NGFR/p75 NTR (Reis-Filho et al, 2006b) and the small heat shock protein a-basic-crystallin (ab-crystallin) (Moyano et al, 2006) that were commonly expressed in basal-like tumors are predictors of good prognosis and poor survival, respectively, in breast cancer patients independently of other prognostic markers. Finally, there is a group of other markers more frequently expressed in BRCA1 tumors that are not basal/ myoepithelial markers but that have been proposed as markers associated with the basal-like phenotype: cyclin E, p53, Skp2 and negativity for p27 (Signoretti et al, 2002;Nielsen et al, 2004;Palacios et al, 2004;Foulkes et al, 2004a;Lakhani et al, 2005).…”
Section: Basal Epithelial Markersmentioning
confidence: 99%